2020
DOI: 10.1186/s43042-020-00096-y
|View full text |Cite|
|
Sign up to set email alerts
|

Extended blood group profiles for Malays, Chinese, and Indians in Peninsular Malaysia

Abstract: Background Blood group antigens are immunogenic polymorphic molecules presented on the surface of RBCs. This study aimed to determine extended blood group profiles (ABO, Rhesus, Kell, Kidd, Duffy, MNS, Cartwright, Dombrock, Colton, Lutheran, and Vel) in Malays, Chinese, and Indians in Peninsular Malaysia. Results Here, ABO Type O, DCCee, MNs, and Fy (a+b−) were the most frequent major blood group phenotypes in all three ethnic groups. Other minor blood group systems distributed differently across these ethnic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…The CO*A and CO*B allele frequencies in Thai and other populations are shown in Table 3 . The CO*A and CO*B frequencies among Thais were similar to previously reported in Thai, 16 Taiwanese, 17 Chinese 6 and Malay-Malaysian 7 populations ( p > 0.05). Significant differences were observed when CO*A and CO*B allele frequencies among Thais compared with South Asian, 6 Southeast Asian, 6 Korean, 6 Japanese, 6 Filipino, 6 French Basque, 10 and Maltese 11 populations ( p < 0.01).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The CO*A and CO*B allele frequencies in Thai and other populations are shown in Table 3 . The CO*A and CO*B frequencies among Thais were similar to previously reported in Thai, 16 Taiwanese, 17 Chinese 6 and Malay-Malaysian 7 populations ( p > 0.05). Significant differences were observed when CO*A and CO*B allele frequencies among Thais compared with South Asian, 6 Southeast Asian, 6 Korean, 6 Japanese, 6 Filipino, 6 French Basque, 10 and Maltese 11 populations ( p < 0.01).…”
Section: Resultssupporting
confidence: 87%
“…The two-tailed Fisher’s exact test of homogeneity was used to determine the differences of their allele frequencies among central, northern and southern Thais and to compare the differences with those reported in other populations. 6 , 7 , 10 , 11 , 16 , 17 A p -value of less than 0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…The Rh-positive was predominant, and the Rh-negative ranged from 3.2% to 66.7%. The absence of Rh-negative in Indonesian, Malaysian, Thai, and Filipino agree with studies, which reported <1% of Rh-negative [38,44,49,[80][81][82]. The higher negativity in Tunisian, Chinese, and Cameroonian is due to their small number.…”
Section: Discussionsupporting
confidence: 86%
“…The Malaysian (n=7) and Somali (n=18) had the frequency of O>A>AB with an absence of B blood group. In Malaysia, the frequency was either O>B>A>AB or O>A>B>AB [43,44]. In Somalia, the frequency was O>A>B>AB [45].…”
Section: Discussionmentioning
confidence: 99%
“…This observation was taken to indicate that the admixture fraction in the contemporary population was around 0.50. Hajar et al (2020) have recently examined the interface between population genetics and human health as it relates to Austronesian populations. For example, they point to the significance of blood group loci as important markers of transfusion success including Kidd Jk (a-b+) and Duffy Fy (a+b+) which are relatively common in this ethnic group but less common in others.…”
Section: Some Illustrative Examplesmentioning
confidence: 99%